A case study of state-level leadership in the American West. Issue 1 (2nd January 2020) - Speciale, Megan; Goodrich, Kristopher M.
ABSTRACT: The authors report on the findings of case study research, using phenomenological analysis, of eight counseling professionals interviewed in a Western state about the experiences of counseling leadership related to a state counseling association. Participants reported their experiences in leadership in three broad ways: professional identity development, leadership sustainability, and personal barriers/supports to leadership involvement. Implications of findings will be discussed.